Glucose-1,6-bisphosphate: A new gatekeeper of cerebral mitochondrial pyruvate uptake - Motahareh Solina Safari; Priska Woerl; Carolin Garmsiri; Dido Weber; Marcel Kwiatkowski; Madlen Hotze; Louisa Kuenkel; Luisa Lang; Matthias Erlacher; Ellen Gelpi; Johannes A. Hainfellner; Gottfried Baier; et al. (Elsevier, 2024)
Objective: Glucose-1,6-bisphosphate (G-1,6-BP), a byproduct of glycolysis that is synthesized by phosphoglucomutase 2 like 1 (PGM2L1), is particularly abundant in neurons. G-1,6-BP is sensitive to the glycolytic flux, due to its dependence on 1,3-bisphosphoglycerate as phosphate donor, and the energy state, due to its degradation by inosine monophosphate-activated phosphomannomutase 1. Since the exact role of this metabolite remains unclear, our aim was to elucidate the specific function of G-1,6-BP in the brain. Methods: The effect of PGM2L1 on neuronal post-ischemic viability was assessed by siRNA-mediated knockdown of PGM2L1 in primary mouse neurons. Acute mouse brain slices were used to correlate the reduction in G-1,6-BP upon ischemia to changes in carbon metabolism by 13C6-glucose tracing. A drug affinity responsive target stability assay was used to test if G-1,6-BP interacts with the mitochondrial pyruvate carrier (MPC) subunits in mouse brain protein extracts. Human embryonic kidney cells expressing a MPC bioluminescence resonance energy transfer sensor were used to analyze how PGM2L1 overexpression affects MPC activity. The effect of G-1,6-BP on mitochondrial pyruvate uptake and oxygen consumption rates was analyzed in isolated mouse brain mitochondria. PGM2L1 and a predicted upstream kinase were overexpressed in a human neuroblastoma cell line and G-1,6-BP levels were measured. Results: We found that G-1,6-BP in mouse brain slices was quickly degraded upon ischemia and reperfusion. Knockdown of PGM2L1 in mouse neurons reduced post-ischemic viability, indicating that PGM2L1 plays a neuroprotective role. The reduction in G-1,6-BP upon ischemia was not accompanied by alterations in glycolytic rates but we did see a reduced 13C6-glucose incorporation into citrate, suggesting a potential role in mitochondrial pyruvate uptake or metabolism. Indeed, G-1,6-BP interacted with both MPC subunits and overexpression of PGM2L1 increased MPC activity. G-1,6-BP, at concentrations found in the brain, enhanced mitochondrial pyruvate uptake and pyruvate-induced oxygen consumption rates. Overexpression of a predicted upstream kinase inhibited PGM2L1 activity, showing that besides metabolism, also signaling pathways can regulate G-1,6-BP levels. Conclusions: We provide evidence that G-1,6-BP positively regulates mitochondrial pyruvate uptake and post-ischemic neuronal viability. These compelling data reveal a novel mechanism by which neurons can couple glycolysis-derived pyruvate to the tricarboxylic acid cycle. This process is sensitive to the glycolytic flux, the cell's energetic state, and upstream signaling cascades, offering many regulatory means to fine-tune this critical metabolic step.